Perception of justice, citizens" trust and participation in a democratic Islamic society - Saputra, Bambang (HTS teologiese studies, 2023)
Justice has a high status in Islamic societies, and as one of the most important human ideals, has long been the focus of thinkers and researchers. In fact, when the citizens do not understand the presence of justice in the behaviour of the officials of their society, their trust in the current procedures, and consequently the public participation will be affected. Considering the importance of the subject, the present study has been conducted with the aim of investigating the effect of perception of justice on citizens’ trust and participation in the creation of a democratic Islamic society. The statistical population of this research included 3578 Indonesian Muslim citizens in 2022, and the research questionnaires were distributed among them. Data analyses were done using Statistical Package for the Social Sciences (SPSS) and Linear Structural Relations (LISREL) statistical software. The results of statistical analyses indicated that the perception of Islamic justice does not have a significant effect on the participation of Muslims in creating a democratic Islamic society. In addition, the perception of Islamic justice has a positive effect on the trust in officials of the Islamic society. Moreover, trust in the officials of the Islamic society positively affects the citizens’ participation in creating a democratic Islamic society.Contribution: According to the results of this research, it is necessary for the officials of the Islamic society to use all their efforts in creating a justice-oriented Islamic society in order to create trust among the citizens, and to involve Muslims in development decisions and to establish democratic Islamic society.